Implementasi Metode UMMI dalam Pembelajaran Al-Qur’an untuk Meningkatkan Kualitas Bacaan Siswa - Hartadi, Hartadi; Subando, Joko (TSAQOFAH, 2026)
Although the Ummi Method has been widely implemented in Qur’an learning, studies that specifically analyze its planning, implementation, evaluation, supporting factors, and obstacles in improving students’ reading quality still need to be strengthened. This study aims to analyze the implementation of the Ummi Method in Qur’an learning to improve students’ reading quality, particularly in the aspects of makhraj al-huruf accuracy, mastery of tajwid rules, reading fluency, recitation rhythm, and self-confidence. This study used a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with school leaders, Qur’an teachers, and students, as well as documentation study. Data analysis was conducted through data reduction, data display, conclusion drawing, and source triangulation. The results showed that the Ummi Method contributed to improving the accuracy of makhraj al-huruf, the application of tajwid, reading fluency, recitation rhythm, and students’ self-confidence in reading the Qur’an. The effectiveness of this method was supported by structured learning stages, teacher certification, standardized teaching materials, periodic evaluation, individual and classical learning strategies, and parental involvement. The obstacles identified included differences in students’ initial reading abilities, limited learning time, and variations in teacher competence. The conclusion of this study affirms that the Ummi Method is an effective pedagogical approach for improving the quality of Qur’an reading through systematic, gradual, and evaluation-oriented learning. The implications of this study include the importance of strengthening teachers’ professional development, providing adequate learning resources, and developing a continuous assessment system to support the sustainable improvement of Qur’an literacy.